AWARENESS REGARDING PERSONAL PROTECTIVE EQUIPMENT USE AMONG HEALTH CARE PROVIDERS IN VARIOUS TERTIARY HOSPITALS ACROSS PAKISTAN DURING COVID-19 PANDEMIC - Kashif, Sanum; Pervaiz, Erum; Azam, Faisal; Waqar, Tahira; Babar, Ayesha; Gul, Ambreen (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the awareness of Personal Protective Equipment usage, among health care providers.Study Design: Cross sectional study.Place and Duration of Study: Tertiary care hospitals across Pakistan, from May 2020 to May 2020 by convenient sampling method.Methodology: A total of 74 responders from different health care setups completed a questionnaire-based survey on the knowledge and practice regarding personal protective equipment usage among healthcare providers. The questionnaire was designed by the help of central disease control (CDC) guidelines and its reliability and validity check by SPSS. Convenient sampling was used for data collection and frequencies and percentages were used to present distribution of responses. WHO sample size calculator (2.2a for population proportions) was used for sample size calculation from previous study 23. Data was tabulated in excel and SPSS 17 was used for Descriptive Statistics.Results: The overall awareness among healthcare providers about PPE use in COVID-19 was not satisfactory with 40.5% reported correct answers. About 54 (75%) of responders had been in contact with confirmed or suspected COVID-19 patients. Regarding kind of Personal Protective Equipment use, 41 (58.6%) knew the correct sequence of donning as per Central Disease Control guidelines and only 21(30%) knew the correct sequence of doffing.Conclusion: The current survey concluded that although majority of responders had fair knowledge regarding COVID-19, yet many knowledge gaps were there, regarding proper donning and doffing technique of PPE. Therefore continuous health education and training programs according to the recent guidelines by CDC and WHO, at all health.......